Exploring the impact of digital professionalism awareness training on dental undergraduate students. (27th September 2020) - Gormley, Mark; Collins, Laura; Schofield, Susie; Neville, Patricia
Abstract: Introduction: Since the publication of GDC guidance, there have been small, but rising numbers of Fitness to Practise (FtP) cases made against qualified dentists, relating to the use of social media. Prior to graduation, dental students currently receive training in the appropriate use of social media, but more work is needed to determine the most effective methods do this. The aim of this study is to explore the impact of the digital professionalism awareness training provided at one UK‐based institution. Materials and Methods: In year 2, a "brown envelope" is compiled using an online publicly available Facebook profile search for every student. All year 2 to 5 dental undergraduate students at one UK dental school who had completed the "brown envelope" were invited to participate in focus groups to examine its impact on behaviour change. A qualitative framework analysis method was applied to the transcripts. Results: Eleven dental undergraduate students participated in two focus groups. All students had experienced the "brown envelope" intervention. Four main themes emerged, including: a clear expression of dental student autonomy and rejection of regulation; that online activity in dentistry is different to medicine; that the intervention is useful and changed online behaviour; and constructive suggestions for improving training. Conclusion: The interactive "brown envelope" intervention for digital professionalism awareness training was well received and appeared to result in actionable behavioural change on student profiles (eg alterations in privacy settings or restricting access to their own "friends lists").